Synthesis, molecular docking and QSAR study of thiazole clubbed pyrazole hybrid as α-amylase inhibitor. Issue 1 (2nd January 2021) - Duhan, Meenakshi; Singh, Rahul; Devi, Meena; Sindhu, Jayant; Bhatia, Rimpy; Kumar, Ashwani; Kumar, Parvin
Abstract: In search of potent α-amylase inhibitors, herein we report the synthesis, molecular docking and QSAR study of some thiazole clubbed pyrazole hybrids (TCPH) i.e., 1-((1-phenyl-3-aryl-1 H -pyrazole-4-yl)methylene)-2-(4-arylthiazole-2-yl)hydrazine (4a–4r) as an α-amylase inhibitors. Among the different analogues, compounds 4g and 4h were found to be most potent at 50 µg/mL with 89.15% and 88.42% of inhibition. The Monte Carlo optimisation method was applied to build robust QSAR models for the prediction of percentage inhibition of TCPH at different concentration with various statistical parameters. The Simplified Molecular Input Line Entry System (SMILES) was applied to symbolise the molecular structure, descriptor calculation and model development. The role of the index of ideality correlation (IIC) was also studied which revealed a model for split 3 as a leading model with best R 2 i.e., 0.9198 . The compound 4l at different concentration (TCPH11, TCPH29 and TCPH47) was outside the applicability domain (AD) for the developed QSAR models for split 4 only. The SMILES attributes at three different concentrations were also detected. These attributes are the promoters of percentage increase/decrease in inhibition efficiency of the inhibitors. The docking simulation of most active compounds (4g and 4h) were performed within the active site of Aspergillus oryzae α-amylase (PDB ID: 7TAA ) to analyse the binding conformation and interactions responsible for their activity. As a result, it was found that the binding interactions found between 4g, 4h and α-amylase were similar to those responsible for α-amylase inhibition by acarbose. Communicated by Ramaswamy H. Sarma